ACTIVITY OF SUPEROXIDE DISMUTASE ENZYME IN EARLY AND ADVANCED STAGES OF NASOPHARYNGEAL CARCINOMA - Gunterus Evans; Abdul Kadir; Riskiana Djamin; Abdul Qadar Punagi; Sutji P. Rahardjo; Mochammad Hatta (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2019)
Introduction:Nasopharyngeal cancer (NPC) ranks - fourth among all cancers in Indonesia. Objective:This study aimed to determine the levels of SOD in patients with NPC. Material and methods : This was a cross sectional study of analytic observational, using consecutive sampling, with 45 patients with NPC and 15 controls. Results: Average of SOD enzyme levels were higher in the NPC patient group (± 1877.87224 1137.119495) compared with the control group (± 441.42120 320.355669) (p <0.05). SOD enzyme levels were higher in advanced stage ± 2060.67363 1179.147923 compared with early stage ± 1338.86685 680.958439 (p <0.05). Conclusion: The level of SOD enzyme in patients with nasopharyngeal cancer is higher than in the control group, and the level is higher in the advanced stage group than in the early stage group.